2015
DOI: 10.15537/smj.2015.3.10683
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of infant burn in Eastern Saudi Arabia

Abstract: Objectives:To identify the epidemiology, pattern, outcome, and impact of infant burns in Eastern Saudi Arabia.Methods:We conducted a retrospective review of admitted infants charts over 4 years (2008-2013) at the Burn Unit of King Fahad Hospital, Hofuf, Al-Ahsa, Saudi Arabia. The charts were reviewed for age, gender, etiology, site of injury, total body surface area (TBSA), depth of burn, hospital stay, and discharge status.Results:The total number of admissions to the Burn Unit was 510 cases. Out of these cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 7 publications
(26 reference statements)
1
11
0
Order By: Relevance
“…DFB was the cause with highest prevalence in our study, this is in consistency with published data (7,13,17,18) and liquid (scald) burns were reported as the second highest. There were some suicide attempts reported, which goes with previous studies (9,11,13,19). Electrical burns were reported in only 3.1%; in this study, electrical burns were due to high voltage electrical current, which was the same situation in developed countries (16,34).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…DFB was the cause with highest prevalence in our study, this is in consistency with published data (7,13,17,18) and liquid (scald) burns were reported as the second highest. There were some suicide attempts reported, which goes with previous studies (9,11,13,19). Electrical burns were reported in only 3.1%; in this study, electrical burns were due to high voltage electrical current, which was the same situation in developed countries (16,34).…”
Section: Discussionsupporting
confidence: 81%
“…Determining that environmental element as the location of the incident varies, helps direct preventive programs as well as emphasize safety measures to be adopted in various environments. The home environment is considered the commonest location of incidence (7,(17)(18)(19)(20), it is suggested that the kitchen contains the highest risk of fire since gadgets are operated on fossil fuel; ethanol gas remains to be adopted by the government and society as the main choice for heating and cooking. Identifying the type of burns experienced more frequently will also guide efforts in developing a specialized efficient preventive program.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 5 ] Applying water (10–15°C) for 20–30 min as first aid for burns is considered the most appropriate step. [ 6 7 8 9 10 11 ] According to a study conducted in Saudi Arabia, most burn injuries occur in the pediatric age group and at home. Scald injuries are the most common type of burn injuries, whereas injuries caused by flames rank second.…”
Section: Introductionmentioning
confidence: 99%
“…[ 15 ] To the best of our knowledge, studies assessing the awareness and knowledge of burn first aid among healthcare workers have not been conducted in Saudi Arabia yet, although several studies assessing the level of first aid knowledge regarding burns have been conducted worldwide among individuals other than healthcare workers. [ 5 6 7 8 9 10 11 12 13 14 15 ] Therefore, we aimed to identify and assess the level of awareness and knowledge of first aid of burns and the association between the overall knowledge and sociodemographic variables among healthcare worker at a university hospital.…”
Section: Introductionmentioning
confidence: 99%